Kolokasi dan Prosodi Semantik pada Kata Capek, Lelah dan Penat Berbasis Linguistik Korpus - Hasbiallah, Zahra Hapriani (Kajian Linguistik dan Sastra, 2026)
Sinonyny is an important component of a language’s lexical system, as words with similar meanings cannot always be used interchangeably in real-life contexts. Language learners often understand differences between synonyms only in terms of their lexical meanings, without considering usage contexts and subtle semantic nuances, which can lead to difficulties in language comprehension. The development of corpus linguistics provides an empirical approach that enables the analysis of word usage based on authentic language data. This study examines the different meanings and usage patterns of the Indonesian words capek, lelah and penat by employing the LCC Indonesia 2023 corpus and a qualitative corpus-based approach. The findings indicate that capek tends to be used subjectively and informally, lelah is used in a neutral and descriptive manner, and penat is used in an emotional and reflective context. These results demonstrate that the synonymy among the three words is contextual in nature and has important implications for lexical semantic studies and vocabulary learning in Indonesian. Abstrak Sinonim merupakan komponen penting dalam sistem kosakata bahasa, karena pilihan kata yang serupa tidak selalu dapat menggantikan satu sama lain dalam kehidupan nyata. Seringkali, orang yang mempelajari bahasa hanya memahami perbedaan sinonim berdasarkan makna leksikalnya, tanpa mempertimbangkan konteks penggunaan dan nuansa makna. Ini menyebabkan masalah dalam memahami bahasa. Perkembangan linguistik korpus memberikan pendekatan empiris yang memungkinkan analisis penggunaan kata yang didasarkan pada data nyata. Kajian ini meneliti penggunaan makna yang berbeda dari kata capek, lelah dan penat dalam bahasa Indonesia dengan menggunakan LCC Indonesia 2023 dan pendekatan kualitatif berbasis korpus. Hasil analisis menunjukkan bahwa capek cenderung digunakan secara subjektif dan informal, lelah digunakan secara netral dan deskriptif, dan penat digunakan secara emosional dan reflektif. Hasil menunjukkan bahwa sinonimi ketiga kata tersebut bersifat kontekstual dan penting untuk studi semantik leksikal dan pembelajaran kosakata dalam bahasa Indonesia.